TAFSIR SURAT LUQMAN PERSPEKTIF KH BISRI MUSTHOFA DALAM TAFSIR AL-IBRIZ - Lilik Faiqoh; M Khoirul Hadi al-Asy’Ari (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2017)
This research is based on library research. this study aims to reveal the interpretation of al-Luqman according to KH. Bisri Mustofa. Luqman's teaching is in accordance with the Javanese lifestyle that forms a harmonious life. this is illustrated in a way to explain it that is easily understood and able to link the content of the Qur'an with the Javanese thinking. the content analysis approach is used to explain the concept of mauizah in Surat al-Luqman, its relation to Javanese cultural tradition in KH. Bisri Mustofa’a perspective, and historicity to study the history of al-Luqman's letter. in this study, it is known that there is an interesting hierarchy in KH. Bisri Mustofa’s interpretive strategy.